Recent Progress in Visible-Light-Mediated S–N Bond Cleavage for Intermolecular Two-Component Dual Functionalization - Zhao, Yu; Xuan, Jun (Synthesis, 2025)
Sulfur- and nitrogen-containing functional groups are fundamental constituents of bioactive molecules and pharmaceuticals, exhibiting diverse pharmacological activities. Recent advances in visible-light-mediated photochemistry have enabled more sustainable and efficient synthetic approaches. This review highlights the emerging strategy of difunctionalization via S–N bond cleavage using bifunctional reagent under visible light irradiation. Key reactions discussed include imino-sulfonylation, imino-sulfamoylation, thiocyanato-imination, and related processes, which enable the simultaneous introduction of sulfur and nitrogen functionalities into alkenes, alkynes, and strained ring systems. Mechanistic pathways involving energy transfer or single-electron transfer facilitate selective radical generation and subsequent cross-coupling, offering broad substrate scope and excellent functional group tolerance. This review provides a critical analysis of current methodologies and outlines future directions for the continued advancement of this rapidly evolving field.
Keywords: Visible-light mediate; Energy transfer; Radical reaction; S–N bond cleavage; Bifunctional reagent